Alcohol and Drug Abuse Resource Utilization in the ICU. (September 2019) - Cervellione, Kelly L; Shah, Aashir; Patel, Mahendra C; Curiel Duran, Laura; Ullah, Tofura; Thurm, Craig
Alcohol and drug abuse continue to be major causes of morbidity and mortality and have significant social and economic ramifications. Studies have shown that for every 1 spent on substance use disorder treatment, 4 are saved on healthcare costs. Characterizing the healthcare resource utilization of these patients may shed light on the burden of disease and opportunities for intervention. A retrospective chart review of all patients admitted to the ICU between July 1, 2017 and December 31, 2017 was completed. Variables regarding demographic and clinical characteristics as well as healthcare resource utilization were collected. Of 737 admissions to the ICU, 158 (21%) were due to acute or chronic complications of alcohol or drug abuse. Even though alcohol and drug users were significantly younger (average age 50 years) than the general ICU cohort (average age 66 years), resource utilization was similar between these patients. The median length of stay in the ICU was similar. The number of patients transferred to in-patient rehab was low (8%), and all of those were due to comorbid psychiatric illness. The total hospital charges for the alcohol and drug abuse cohort was over 7 million dollars for the 6 months observed. A significant number of patients had at least one ER visit (49%) during the previous year, and most of these had numerous visits. ICU resource utilization by patients with acute and chronic sequelae of drug or alcohol abuse disorders continues to be high. These patients utilize resources at rates similar to an older group with other disease processes. Patients are unlikely to receive intervention for their disorder unless they have a comorbid psychiatric illness. Patients admitted to the ICU with alcohol or drug-related illness were frequently seen in the ER or were admitted to the hospital in the year prior to ICU admission, providing opportunities for intervention.